Assessment of Ki-67 expression in cases of prostatic carcinoma and its correlation with clinical outcomes - Sumaira Siddiqui (Indian Journal of Pathology and Microbiology)
Background: Treatment decisions after diagnosis of clinically localized prostate cancer are difficult due to variability in tumor behavior. As there is a high prevalence of low-grade prostate cancer with an indolent course, we need improved markers of prostate cancer lethality in order to reduce the overtreatment. In the current study, we assessed Ki-67 expression in cases of prostate carcinoma and correlated its expression with clinical outcomes. Materials and Methods: It was a single-center retrospective descriptive type of study. A total of 50 cases were included. Diagnosed cases of adenocarcinoma on Transurethral Resection of the Prostate (TURP) chips and Trucut prostatic biopsies (Archival biopsy specimens) for whom five years follow-up was available from record files and/or telephonic interviews were included. The clinical outcomes (rate of distant metastases, disease specific survival, and overall survival) over a period of five years were recorded. Results: In the current study, 78% of the cases of carcinoma prostate were positive for Ki-67 expression. The mean Ki-67 staining index was 15.22% among the cases. The cases with High Ki-67 Staining index had a significantly higher rate of distant metastasis, poor disease-specific survival, and overall survival compared to cases with low Ki-67 staining index. Conclusion: Ki-67 can be used along with the other established prognostic parameters to assess the lethality of prostate cancer.